Desenvolvimento do Atlas da Questão Agrária Brasileira: análise da dinâmica territorial recente da agropecuária brasileira (2006-2012) e da participação da agricultura camponesa na produção do campo (2006) - Ribeiro, Edson Sabatini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This monograph is part of the works developed in the Scientific Initiation aimed at updating and improving the Atlas of Brazilian Agrarian Question - AQAB. For pioneering and scope of work-matrix, the objective this first part focused on the development of issues related to agricultural production, being drawn maps with data from the Municipal Agricultural Production-PAM 2012; Municipal Livestock Research-PPM 2012; Production of Vegetable Extraction and Forestry-2012, all analyzed from bibliographic review and joint interpretation of tables and graphs. Pari passu, this topic allowed the development of studies on peasant farms, because they are correlated subjects. Peasant farmers produce large portion of the food served to the population. Its features are its mode of production in the field, the way in which the activities take place within the family, the struggle for their social reproduction and by the earth, the practice of polyculture, preservation of the environment and the genetic diversity of species. The surplus production is sold on the market to meet other family demands unmet by production on their properties. We understand that both terms; Peasant or Farmer, refer to the same subject, but with different interpretations of their way of social reproduction and market relations...

Esta monografia é parte dos trabalhos desenvolvidos na Iniciação Científica visando à atualização e aprimoramento do Atlas da Questão Agrária Brasileira - AQAB. Pelo pioneirismo e abrangência do trabalho-matriz, o objetivo desta primeira parte se concentrou no desenvolvimento dos temas ligados à produção agropecuária, sendo elaborados mapas com dados da Produção Agrícola Municipal-PAM 2012; Pesquisa Pecuária Municipal-PPM 2012; Produção da Extração Vegetal e Silvicultura 2012, todos analisados a partir de revisão bibliográfica e da interpretação conjunta de tabelas e Gráficos. Pari passu, por serem assuntos correlatos este tema permitiu o desenvolvimento de estudos sobre a Agricultura Camponesa. Grande porção dos alimentos servidos à população é produzida pelos camponeses. Suas características são seu modo de produção no campo voltado para o sustento da família, a maneira de como as atividades se desenvolvem no núcleo familiar, a luta pela sua reprodução social e pela terra, a prática da policultura, a preservação do meio ambiente e da diversidade genética das espécies. O excedente da produção é comercializado no mercado para atender outras demandas familiares, não supridas pela produção em suas propriedades...
Keywords: Geografia; Agricultura; Agropecuaria; Políticas públicas; Camponeses; Geography